A College Entrance Essay Exam Intervention for Students With High-Incidence Disabilities and Struggling Writers. (November 2021) - Ray, Amber B.; Graham, Steve
High school students with high-incidence disabilities and struggling writers face considerable challenges when taking writing assessments designed for college entrance. This study examined the effectiveness of a writing intervention for improving students' performance on a college entrance exam, the writing assessment for the ACT. Students were taught a planning and composing strategy for successfully taking this test using the self-regulated strategy development (SRSD) model. A true-experiment was conducted where 20 high school students were randomly assigned to a treatment ( n = 10) or control ( n = 10) condition. Control students received ACT math preparation. SRSD instruction statistically enhanced students' planning, the quality of their written text (including ideas and analysis, development and support, organization, and language use), the inclusion of argumentative elements in their compositions, and the use of transition words in written text. Limitations of the study, future research, and implications for practice are discussed.